Re-charge Mind melalui Konseling Kelompok untuk Mengurangi Burnout Akademik pada Siswa SMA Negeri 5 Palembang - Itryah Itryah; Audya Sasi Putria Fazrin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The Re-Charge Mind program was held as a community service program to reduce academic burnout in class XII students of SMA Negeri 5 Palembang through group counseling based on Cognitive Behavioral Therapy (CBT). This study used a descriptive quantitative method with a pre-test and post-test design and was supported by observation and interviews to assess changes in behavior and psychology. The results showed that all subjects experienced a decrease in burnout levels; Subject C from high to moderate (35.7%), Subject A from moderate to low (50%), and Subject L from moderate to low (66.7%) with an average decrease of 50.8%. Emotional exhaustion and negative thoughts have decreased significantly, while self-awareness, motivation, and emotion regulation have increased. This program proves the effectiveness of CBT as one of the practical interventions in improving the mental health and quality of learning of students.